Phytochemical evaluation and antioxidant potential of Echinodorus macrophyllus extracts - Antônio Lisboa Ribeiro; Marcus Vinícius Gonçalves Antunes; Christiane Fátima Oliveira; Rafaela Camargos Rodrigues Machado; Rafael Rodrigues Silva; Brayan Jonas Mano-Sousa; Lucas Santos Azevedo; Joaquim Mauricio Duarte-Almeida; Luciana Alves Rodrigues dos Santos Lima (Brazilian Journal of Pharmaceutical Sciences)
Abstract Belonging to the Alismataceae family, Echinodorus macrophyllus, known in Brazil as “chapéu de couro”, is popular in the food industry, where it is used in teas and infusions. The objective of this study was to evaluate the active chemical compounds in the powder of E. macrophyllus leaves extracted by two different methods (Soxhlet [SXT] and ultrasound-assisted extraction [UAE]), quantify the total phenolic compound (TPC) and total flavonoid (TFC) content, and evaluate the antioxidant potential and larvicidal activity. The SXT extraction was the most efficient (6.05% yield). Analysis by thin-layer chromatography (TLC) and high-performance liquid chromatography with a diode array detector (HPLC-DAD) evidenced the presence of cinnamic acid derivatives, flavones, and flavanones in the extracts. The TPC was higher in the SXT extract (7.71±0.05 µg GAE/mL). However, there was no significant difference in TFC. The SXT extract exhibited greater antioxidant potential according to the ferric reducing antioxidant power (FRAP) method (IC50=3.37±0.45 µg/mL), while the UAE extract showed higher activity using 1,1-diphenyl-2-picrylhydrazyl (DPPH) (IC50=42.16±5.79 µg/mL). Both extracts were nontoxic to Artemia salina, suggesting the potential health benefits of this plant, which is rich in phenolic compounds and diverse pharmacological properties.